COUNSELING AND INTRODUCTION OF THE ORIGIN TRADITIONAL LIVELIHOOD OF DAYAK TRIBES IN TUMBANG LINTING VILLAGES AT CENTRAL KALIMANTAN: PENYULUHAN DAN PENGENALAN MATA PENCAHARIAN TRADISIONAL ASLI SUKU DAYAK DI DESA TUMBANG LITING KALIMANTAN TENGAH - Ahmad Irfan Musthafa; Iis Daliati Maria Aprilia; Miranti Aditia; Yella Saputri; Offeny Offeny; Ahmad Saefullah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
This research was conducted to determine the livelihoods of the Dayak tribe in the village of Tumbang Liting, Katingan Regency, Central Kalimantan Province, and how their current existence is in meeting the needs of the Tumbang Liting village community. The method used is descriptive qualitative. Data sources are primary data and secondary data. The data collection procedure uses observation, interviews, and documentation, while data analysis includes data collection, data reduction, data presentation, and data collection using triangulation techniques. The results showed that the traditional Dayak livelihoods in Tumbang Liting village still exist or are still widely cultivated by the people of Tumbang Liting village today. The livelihoods in Tumbang Liting village are pretty diverse, ranging from State Civil Apparatus (ASN), honorary workers, farmers/cultivators, planters, fishers, rattan cutters, and others. Included in the livelihoods of the Dayak tribe are fishers, cultivators, and rattan cutters. One of the main livelihoods of the Dayak tribe in Tumbang Liting village, which is still widely used by the community, is fishermen because they still meet the daily needs of the local community, besides that there is still much fish from natural products, and the selling price is relatively high, not only to meet the needs of the community. Tumbang Liting village, but also exported or sold outside the village, such as in the city of Kasongan and its surroundings. Traditional Dayak livelihoods provide teaching in meeting human needs in harmony with how to protect nature.